2007
DOI: 10.1139/w06-093
|View full text |Cite
|
Sign up to set email alerts
|

Agrichemical impact on growth and survival of non-target apple phyllosphere microorganisms

Abstract: The impact of conventional agrichemicals commonly used in New Zealand apple production on non-target, culturable phyllosphere microbial populations was studied in the laboratory (agar, leaf, and seedling assays) and field (apple orchard). Morphologically distinct bacteria (three), yeasts (five), and filamentous microfungi (two) were used as indicator species. The agar assay showed that agrichemical toxicity to microorganisms was dependent on product type, product rate, and organism studied. While the fungicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Actually, on the basis of the findings of a pesticide program on the non-target epiphytic microbial population of apple leaves, it was reported that populations of bacteria, filamentous fungi, yeast, and actinomycetes varied annually and were reduced 10- to 1,000-fold in 1976 and up to 50-fold in 1977 on pesticide-treated leaves [5]–[6]. A similar study on the agrichemical impact on the growth and survival of non-target microorganisms in the phyllosphere of apple trees revealed that repeated agrichemical applications reduced the in planta microbial population 10- to 10,000-fold, suggesting that agrichemicals could affect the non-target, culturable surface microorganisms [7]. A seasonal comparative study of the effect of organic and integrated production systems on the culturable fungi of stored Golden Delicious apples was conducted in Switzerland; the findings revealed that organically produced apples had significantly higher frequencies of filamentous fungi, abundance of total fungi, and higher taxon diversity than the apples produced by integrated systems [8].…”
Section: Introductionmentioning
confidence: 82%
“…Actually, on the basis of the findings of a pesticide program on the non-target epiphytic microbial population of apple leaves, it was reported that populations of bacteria, filamentous fungi, yeast, and actinomycetes varied annually and were reduced 10- to 1,000-fold in 1976 and up to 50-fold in 1977 on pesticide-treated leaves [5]–[6]. A similar study on the agrichemical impact on the growth and survival of non-target microorganisms in the phyllosphere of apple trees revealed that repeated agrichemical applications reduced the in planta microbial population 10- to 10,000-fold, suggesting that agrichemicals could affect the non-target, culturable surface microorganisms [7]. A seasonal comparative study of the effect of organic and integrated production systems on the culturable fungi of stored Golden Delicious apples was conducted in Switzerland; the findings revealed that organically produced apples had significantly higher frequencies of filamentous fungi, abundance of total fungi, and higher taxon diversity than the apples produced by integrated systems [8].…”
Section: Introductionmentioning
confidence: 82%
“…A few studies showed that fungicide applications can reduce the diversity and alter the composition of the foliar microbial community (Gu et al, 2010; Moulas et al, 2013; Cordero-Bueso, Arroyo & Valero, 2014; Karlsson et al, 2014). However, several other studies showed that the foliar fungal communities of grapevine are highly resilient to some chemical or biological pesticides (Walter et al, 2007; Perazzolli et al, 2014; Ottesen et al, 2015). Further research is required to assess the influence of fungicide applications on the observed decline in the richness of foliar fungal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical location has been identified as a main driver in a lettuce field (Rastogi et al, 2012), but not in trees (Redford et al, 2010). Other factors are the growing season (Rastogi et al, 2012), nitrogen fertilization (Ikeda et al, 2011), and pesticide application (Moulas et al, 2013;Walter et al, 2007;Zhang et al, 2009). …”
Section: Driving Factors Of the Rhizosphere And Phyllosphere Microbiomesmentioning
confidence: 99%